Case report: Laryngeal trauma at Juba Teaching Hospital, South Sudan - Justin Rubena Lumaya; Jino David; Natali Tong (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2019)
Laryngeal injury is a life-threatening condition. Laryngeal trauma is very rare among children and the severity may be easily missed by the inexperienced clinician. A high index of suspicion is essential because some patients do not present with the classic symptoms and signs. Recent advances in the management of laryngeal trauma using endoscopes have significantly reduced morbidity and mortality. We present a case of a young boy who had blunt laryngeal trauma and sustained a fracture to the thyroid cartilage with an associated mucosal tear.